The Prevalence of Scopulariopsis sp. and Penicillium sp. in African Pygmy Hedgehogs (Atelerix albiventris) Skins in a Farm in Bogor District of Indonesia - Rahmadani, Satria Tegar; Budiono, Novericko Ginger; Nurhidayat (Media Kedokteran Hewan, 2025)
This research aims to detect the prevalence of Scopulariopsis sp. and Penicillium sp. in African pygmy hedgehogs (Atelerix albiventris) bred at Golden Dhonje Farm, Bogor District. Twenty hedgehogs were sampled to detect the presence of Scopulariopsis sp. and Penicillium sp. The clinical signs in the sampled African pygmy hedgehogs include alopecia, crusty skin, and dermatitis. The presence of the fungus was confirmed by taking skin samples and then culturing them on Potato Dextrose Agar (PDA) supplemented with chloramphenicol and cycloheximide. Macroscopic and microscopic morphology were observed to identify the two fungal genera. Twenty hedgehogs were sampled, and the results showed that eight of them (40%) were infected with Scopulariopsis sp., six (30%) were infected with Penicillium sp., and four (20%) were co-infected with both species. The total prevalence of hedgehogs affected by these fungi is 90%. This study found differences in infection rates of Scopulariopsis sp. and Penicillium sp. among different age groups and sexes. This study is the first to isolate Scopulariopsis sp. and Penicillium sp. from the skins of African pygmy hedgehogs in Indonesia, which are potential zoonotic pathogens. Further research is needed to expand the sample area, identify other types of fungi, and enhance the understanding of fungal diseases in African pygmy hedgehogs, thereby ensuring the safety of these animals in Indonesia.